An Oleuropein β-Glucosidase from Olive Fruit Is Involved in Determining the Phenolic Composition of Virgin Olive Oil - Velázquez-Palmero, David; Romero-Segura, Carmen; García-Rodríguez, Rosa; Hernández, María L.; Vaistij, Fabián E.; Graham, Ian A.; Pérez, Ana G.; Martínez-Rivas, José M. (Frontiers in Plant Science, 2017)
Phenolic composition of virgin olive oil is determined by the enzymatic and/or chemical reactions that take place during olive fruit processing. Of these enzymes, β-glucosidase activity plays a key role in the transformation of the phenolic glycosides present in the olive fruit, generating different secoiridoid derivatives. The main goal of the present study was to characterize olive fruit β-glucosidase genes and enzymes responsible for the phenolic composition of virgin olive oil. To achieve that, we have isolated an olive β-glucosidase gene from cultivar Picual (OepGLU), expressed in Nicotiana benthamiana leaves and purified its corresponding recombinant enzyme. Western blot analysis showed that recombinant OepGLU protein is detected by an antibody raised against the purified native olive mesocarp β-glucosidase enzyme, and exhibits a deduced molecular mass of 65.0 kDa. The recombinant OepGLU enzyme showed activity on the main olive phenolic glycosides, with the highest levels toward oleuropein, followed by ligstroside and demethyloleuropein. In addition, expression analysis showed that olive GLU transcript level in olive fruit is spatially and temporally regulated in a cultivar-dependent manner. Furthermore, temperature, light and water regime regulate olive GLU gene expression in olive fruit mesocarp. All these data are consistent with the involvement of OepGLU enzyme in the formation of the main phenolic compounds found in virgin olive oil.